Flow of funds in the United States, 1939-1953 - Board of Governors of the Federal Reserve System (U.S.); Board of Governors of the Federal Reserve System (U.S.) ([Washington : Board of Governors of the Federal Reserve System (U.S.), 1955)
This book contains a detailed compilation of flow- of- funds system of accounts in the United States economy from 1939-1953.
includes bibliographical footnotes.
usc 14/07/2017
Loans
Keywords: Income; United States